Optimalisasi Sistem Pemilu Melalui Implementasi E-Voting Berbasis Blockchain Dengan Keamanan Kriptografi AES-128 - Suryadi, Usep Tatang; Permana , Ardi; Abidin, Aa Zezen Zaenal; Murdianingsih, Yuli; Carkiman, Carkiman; Faizal, Muhammad (Jurnal Teknologi Informasi dan Komunikasi, 2025)
The general election (Pemilu) is a fundamental element of a democratic system. This study develops and evaluates a blockchain-based e-voting system implementing AES-128 encryption to ensure the confidentiality, integrity, and availability of voting data. The system integrates AES-128 symmetric encryption for data at-rest and SHA-256 hashing at the blockchain layer. Testing was conducted on a simulated dataset containing 100,000 voting records to measure processing time, storage efficiency, and cryptographic resilience against brute-force and data manipulation attacks. Experimental results show an average read/processing time of 24 seconds for 100,000 records under the test server configuration, and theoretical security analysis indicates that brute-forcing AES-128 is impractical with current computational capabilities. The contribution of this research lies in the integrated design of an e-voting system that combines data encryption and distributed storage models with verification mechanisms, thereby enhancing the transparency and auditability of the election process.